"Writing history as a way of life": The life and work of Margaret Garritsen de Vries - Christina Laskaridis (Duke University, Center for the History of Political Economy (CHOPE), 2022)
The name of Margaret Garritsen de Vries may not be the first that pops into people's mind when thinking about the International Monetary Fund. It is through her work, as long-standing official Fund Historian, that those interested in the Fund history will travel through. An operational economist during the first part of her career, her turn to history was the avenue through which she could continue it. Leaving a lasting impression on her colleagues, her institution, and the economics profession overall, she reaped recognition of her pioneering work for furthering the status of women in the profession, receiving prestigious awards and memorial funds set up in her name. The primary aim of this paper is to piece together a brief biography. Studying the life of a woman economist turned historian in an international organization brings to light her contribution as an economist working in a predominantly man's field (international monetary and financial issues), explores her work as a historian - the main area of work for which she gained recognition - and also draw out some of the particularities of women's work in international organization during this period.
Keywords: 330; International Monetary Fund; History of Economics; Gender; Women; Economists in international organisations